THEORETICAL PREREQUISITES OF RECEIVING OF QUALITATIVE METAL PRODUCTION IN PIPE ROLLING - V. I. Timoshpolski; Ju. A. Samoilovich; I. A. Trusova (Литьë и металлургия)
The theoretical suppositions for creation of qualitative metal production in pipe rolling, based on the principles of production of defect less slug on the continuous casting machines, are worked out.